Optimization of Online SP2HP by Investigators in the Tipidkor Unit of Batang Polres to Realize Justice Transparency - Suriono, Ari Ade (Advances in Police Science Research Journal, 2024)
Sp2hp online is a way that is used to support the police chief's precision program, sp2hp online allows reporters to follow the progress of an investigation using only a gadget with the capacity to open the internet. In addition, sp2hp online will make it easier for superiors and leaders to supervise the performance of members, in this case investigators, but this sp2hp online is a problem that occurs at the batang police. Implementation that was less than optimal, plus the delegation of reports on the implementation of sp2hp online to baurmin and not being carried out directly by investigators, as well as the public and investigators who were not used to using sp2hp online made sp2hp online not implemented properly and did not support the chief of police's precision program which had to be implemented by each part of the polri agency, from the smallest to the largest. The purpose of this study was to identify problems related to the implementation of sp2hp online by the batang police satreskrim tipidkor unit. In practice, the research was carried out using a qualitative approach that combined field research and descriptive analysis methods. Based on the results of the research carried out, it shows that the main obstacle to the implementation of sp2hp online at the batang police is the implementation or regulations that are too complicated and the public is not educated about sp2hp online which should be able to facilitate the implementation of communication between investigators and reporters. This is influenced by several factors, both internal and external factors which are owned by the criminal investigation unit of the batang police. Therefore the authors suggest empowering personnel, budget support, as well as facilities and infrastructure capable of supporting the implementation of sp2hp online, increasing cooperation from the internal police to optimize the implementation of sp2hp online at the batang police headquarters by the tipidkor unit. Based on the results of the research carried out, it shows that the main obstacle to the implementation of SP2HP Online at the Batang Police is the implementation or regulations that are too complicated and the public is not educated about SP2HP Online which should be able to facilitate the implementation of communication between investigators and reporters. This is influenced by several factors, both internal and external factors which are owned by the Criminal Investigation Unit of the Batang Police.